Pengaruh Kualitas Pelayanan, Promosi Dan Lokasi Terhadap Minat Masyarakat Menabung Di Bank Syariah Indonesia (BSI) (Studi Pada Masyarakat Kecamatan Merlung) - Fikri Wijaya; Addiarrahman Addiarrahman; M. Taufik Ridho (Al Itmamiy Jurnal Hukum Ekonomi Syariah (Muamalah), 2023)
In this study, there are three factors that influence interest, namely service quality, promotions, location. because these three factors are very closely related to what is felt by the community. This research was conducted to find out whether the factors of service quality, promotion, and location affect people's interest in saving at Bank Syariah Indonesia KFO Mikro Merlung. The type of research used in this research is descriptive quantitative. The population in this study were customers at BSI KFO Micro Merlung, totaling 17,493 people. The number of samples obtained in the field were then processed using the slovin formula, the results obtained were 99 respondents. Based on the results of the data calculation, it is known that service quality has a positive and significant effect on people's interest in saving because the value of tcount ˃ ttable is 4.683 ˃ 1.661 and the resulting significant value is 0.000 ˂ 0.05, promotions have a positive and significant effect on people's interest in saving because the value of tcount ˃ ttable is 3.221 ˃ 1.661 and the resulting significant value is 0.000 ˂ 0.05 and location has a positive and significant effect on people's interest in saving because the value of tcount ˃ ttable is 2.313 ˃ 1.661 and the resulting significant value is 0.000 ˂ 0.05. The results of the F test, namely service quality, promotion, and location simultaneously have a positive and significant effect on people's interest in saving because the value of Fcount ˃ Ftable or 6.365 ˃ 1.661 and the resulting significant value is 0.000 ˂ 0.05. So it can be concluded that simultaneously or simultaneously it influences people's interest in saving. The results of the determination test (R2) on the independent variables, namely service quality, promotion, and location on the dependent variable, namely the public's interest in saving, is 66.2%, while the remaining 33.8% is influenced by other factors outside this variable.